SIMULATION USING REGRESSION ANALYSIS COMPUTED TOMOGRAPHY SIZES OF MAXILLARY SINUS HEALTHY CITY IN YOUNG PEOPLE AND MEN DEPENDING ON ANTHROPO-SOMATOTYPOLOGICAL INDICATORS - Gunas, I.V.; Shkolnik, E.Ya.; Beliaev, Е.V. (World of Medicine and Biology, 2015)
Aim of our work – to build regression models computed tomographic size of maxillary sinuses (MS) in healthy urban young men and men of Podillya, depending on the characteristics of the structure and size of the body.Materials and methodsOn the base of SRC VNMU named after Pirogov conducted anthropometric and computed tomography (CT) study of 7 practically healthy young men aged from 18 to 21 years and 13 practically healthy men aged from 22 to 25 years in the third generation residents Podolsky region of Ukraine.Morphometry of MS included definition: the distance between the most distant lateral points of MS; the distance between the front points of MS; the distance between the rear points of MS; distance between the medial wall of MS (middle wall); the distance between the middle of the front wall and the rear point of MS right and left; the length of the medial wall MS right and left; lateral distance between the point and the midpoint of the medial wall MS right and left; the thickness of the back (lateral) wall of MS (measured in the middle of the wall) to the right and left; thickness of medial wall MS (measured in the middle of the wall) to the right and left; the thickness of the front wall MS (measured in the middle of the wall) to the right and left.Anthropometry carried out in accordance to the scheme Bunak (1941). Cephalometry included measuring the circumference of the head, sagittal curves, the greatest length and width of the head, the smallest width of the head, the width of the face and mandible. Assessment of somatotype conducted by a mathematical scheme by Heath-Carter (2003), and component composition of body weight by formulas Matiegka (1921).Regression models performed using the license package «STATISTICA 6.1».Results. DiscussionsBased on the characteristics of anthropo-somatotypological indicators in healthy young men and men of Podillya reliable regression models constructed for 9 out of 16 possible computerized tomographic parameters of MS with determination coefficient R2 from 0.716 to 0.907.The structure models computed tomographic parameters of MS include cephalometric rates (32.6%), width of distal epiphysis of long bones of the extremities (17.4%), girth body size (13.0%), pelvic size and thickness of skin fat folds (by 8.7%), the longitudinal body size and diameter of the trunk (by 6.5%), indicators component composition of body weight (4.3%) and somatotype components (2.2%).
Keywords: maxillary sinus; anthropometry; regression models; computed tomography; healthy young men